Διαχωρισμός και ανάκτηση πρωτεϊνών και σακχάρων από τυρόγαλο χαλλουμιού με τη χρήση μεμβρανών υπερδιήθησης - Χασιώτης, Στάθης (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
The current thesis investigated the separation and recovery of proteins and sugars from halloumi whey. During the process of halloumi manufacturing, big volumes of whey is produced as waste. The whey is high in organic matter and its processing is a costly process. The objective of the current study was to investigate the separation and the recovery of high added value components (proteins and sugars) as byproducts of halloumi whey. For this purpose, two samples of industrially produced whey were processed using five types of ultrafiltration membranes with different Molecular Weight Cut Offs (MWCO: 100, 50, 20, 2, 1 kDa) under various transmembrane pressures. The experiments were performed in a laboratory size membrane apparatus (Alfa Laval Labunit M10). In the first part of the experiment, ultrafiltration was conducted using three types of membranes cutoff 100, 50 and 20 kDa. Two replicates were performed for each sample and each type of membrane. Retention coefficients and performance parameters were monitored for each experiment. Feed and permeate was collected for analysis. In the second part of the experimental procedure permeate from the 20 kDa membrane was used as feed for the membranes treated with 2 and 1 kDa, and similar procedures as the first part were followed. Performance parameters and coefficients were studied for each experimental combination. Analyses were made for retention of protein, total sugars and total phenols. According to the results, all the membranes had a high retention rate of protein (70-90%). The disadvantages of membranes with smaller MWCO were the relatively high retention of total sugars in the concentrate (20-40%) and the low flux. However, the optimum separation was performed using the 100 kDa membrane which led to ~ 75% of proteins remaining in the concentrate, while ~ 98% of total sugars passed in the filtrate achieving the separation of two components. The optimum operating parameters were at a pressure of 3 bar where the flux was ~ 12 Lm -2h-1 and the relative flux was around 50%.
Keywords: Proteins; Dishes; Πρωτείνες; Χαλούμια; Εδέσματα